Rifting and sediments in the Red Sea and Arabian gulf regions - Rasul, Najeeb M.A; Stewart, Ian C.F (CRC Press, Taylor & Francis Group, 2024)
Rifting and Sediments in the Red Sea and Arabian Gulf Regions is a unique text that covers a wide range of topics related to the tectonics and geology of the Red Sea and Arabian (Persian) Gulf region. This book is a collection of invited and peer-reviewed chapters contributed by active researchers around the world.The topics covered in this book include tectonics, magmatism, and lithology, particularly in the Red Sea area. The book also delves into the sediments and evaporites of the Red Sea and Gulf. As the area around the Arabian Peninsula is prone to earthquakes, the seismic hazard estimated in the Red Sea region is also covered by several chapters. Each chapter presents new data and offers extensive lists of references for the reader to explore further.With the ongoing debates regarding the structure of the Red Sea, this book serves as an excellent resource for researchers and any individuals interested in the geology of these two unique seas